PENINGKATAN PEMAHAMAN SISWA SMP PADA TEKS NARRATIVE MELALUI STRATEGI SEMANTIC MAPPING - Durratul Hikmah; Mohammad Sofyan Adi Pranata (Universitas Islam Balitar, 2020)
Narrative texts imply life lessons in each of their stories. Hence, students are expected to understand the text and capture the moral message of life contained in the text. Reading narrative text needs particular strategy to determine the moral message behind text. One of the strategies is semantic mapping. Semantic Mapping helps teachers direct the students not only to focus on the details of each keyword but also on the structure of the text. It shows a connection between ideas and story components. This study investigated the effectiveness of using semantic mapping strategy for improving students’ reading skill on narrative text. It used a quasi-experimental design. The population of this study was 51 students of SMP Nurul Jadid Paiton Probolinggo consisting of 25 students from class VIII-H as experimental class and 26 students from class VIII-I as control class. In this study, the pre-test, treatments, and post-test given to both experimental and control classes. The data were analyzed by using T-test for using SPSS 16.00 Windows to know the sinificant difference of the students’ reading comprehension text between experimental and control class. The finding showed that semantic mapping strategy is an effective way in improving students’ comprehension on reading narrative text.